2020
DOI: 10.2147/orr.s265905
|View full text |Cite
|
Sign up to set email alerts
|

<p>The Yield of Lumbosacral Spine MRI in Patients with Isolated Chronic Low Back Pain: A Cross-Sectional Study</p>

Abstract: Background The role of routine lumbosacral MRI in patients presented with isolated chronic low back pain (CLBP) is still unclear. Most patients with CLBP will show diverting degenerative changes on MRI. As it is uncertain whether surgical treatment of degenerative MRI changes results in alleviation of back pain or not, the necessity of doing a diagnostic lumbosacral MRI remains questionable. This study aimed to evaluate the yield of lumbosacral MRI among Jordanian patients presented with isolated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 18 publications
(11 reference statements)
0
2
0
Order By: Relevance
“…In our study, most patients who had positive MRI findings underwent conservative management (88%), which means that the MRI did not change the management plan. According to Kanaan et al, multiple randomized clinical trials have shown that early imaging versus conservative treatment without imaging for patients with no red flags does not enhance patient outcomes [15]. Moreover, a 2020 study of 405,965 United States primary care patients found that those who had early MRI were more likely to undergo back surgery (1.48% versus 0.12%) and take prescription opioids (35.1% versus 28.6%), yet they had a higher pain score at one-year follow-up (3.99 versus 3.87) than those who did not get early MRI [21].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In our study, most patients who had positive MRI findings underwent conservative management (88%), which means that the MRI did not change the management plan. According to Kanaan et al, multiple randomized clinical trials have shown that early imaging versus conservative treatment without imaging for patients with no red flags does not enhance patient outcomes [15]. Moreover, a 2020 study of 405,965 United States primary care patients found that those who had early MRI were more likely to undergo back surgery (1.48% versus 0.12%) and take prescription opioids (35.1% versus 28.6%), yet they had a higher pain score at one-year follow-up (3.99 versus 3.87) than those who did not get early MRI [21].…”
Section: Discussionmentioning
confidence: 99%
“…Anxious patients looking for a definitive diagnosis are a major cause of the inappropriate use of imaging [15]. In a survey, 50% of patients believed that everyone with LBP should have imaging, and 72% considered imaging as important [16].…”
Section: Introductionmentioning
confidence: 99%